FAKTOR-FAKTOR YANG MENDORONG ALIH FUNGSI LAHAN SAWAH DI WILAYAH SENTRA PRODUKSI PADI KABUPATEN TANJUNG JABUNG TIMUR - Firmansyah; Aryiansyah, David; Murdy, Saad (JALOW | Journal of Agribusiness and Local Wisdom, 2021)
The study aims to determine the magnitude of the conversion of paddy land to non-paddy land in the area of ​​rice production centers in Tanjung Jabung Timur Regency and to analyze the magnitude of the influence of economic factors, socio-cultural factors, technical factors, environmental factors and policy factors directly or indirectly encourage the occurrence of the function of paddy fields in the area of ​​rice production centers in Tanjung Jabung Timur Regency. The research method used in this study is a survey method with sampling techniques in multi-stage cluster random sampling and path analysis. The conversion of the function of paddy fields to non-paddy fields in Tanjung Jabung Timur Regency varies, ranging from 0.38 ha to 5.00 ha per farmer with an average conversion of 1.56 ha per farmer. The most paddy fields in the Tanjung Jabung Timur Regency rice production center area are mostly converted into palm oil gardens (30.68%). Economic factors, socio-cultural factors, environmental factors, technical factors and government policy factors simultaneously affect the occurrence of land use change in the area of ​​rice production centers in East Tanjung Jabung Regency. While partially only economic factors and government policy factors that affect the conversion of paddy fields in the area of ​​rice production centers in Tanjung Jabung Timur Regency